Altered Risk-Taking Behavior in Early-Stage Bipolar Disorder With a History of Psychosis - Wong, Sandra Chi Yiu; Ng, Mary Chung Mun; Chan, Joe Kwun Nam; Luk, Martha Sin Ki; Lui, Simon Sai Yu; Chen, Eric Yu Hai; Chang, Wing Chung (Frontiers in Psychiatry, 2021)
Altered risk-taking propensity is an important determinant of functional impairment in bipolar disorder. However, prior studies primarily assessed patients with chronic illness, and risk-taking has not been evaluated in the early illness course. This study investigated risk-taking behavior in 39 euthymic early-stage bipolar disorder patients aged 16-40 years who were treated within three years from their first-episode mania with psychotic features and 36 demographically-matched healthy controls using the Balloon Analogue Risk Task (BART), a well-validated risk-taking performance-based paradigm requiring participants to make responses for cumulative gain at increasing risk of loss. Relationships of risk-taking indices with symptoms, self-reported impulsivity, cognitive functions, and treatment characteristics were also assessed. Our results showed that patients exhibited significantly lower adjusted scores (i.e., average balloon pumps in unexploded trials) (p = 0.001), lower explosion rate (p = 0.007) and lower cumulative scores (p = 0.003) than controls on BART, indicating their suboptimal risk-taking performance with increased propensity for risk aversion. Risk-taking indices were not correlated with any symptom dimensions, self-reported impulsivity, cognitive functions or antipsychotic dose. No significant difference was observed between patients with and without antipsychotic medications on self-reported impulsivity or any of the BART performance indices. This is the first study to examine risk-taking behavior in early-stage bipolar disorder with history of psychosis and indicates that patients displayed altered risk-taking with increased risk aversion compared with controls. Further research is needed to clarify longitudinal trajectory of risk-taking propensity and its relationships with psychosis and functional outcome in the early stage of bipolar disorder.